Evaluation of the acceptability and clinical utility of an Arabic-language mindfulness CD in an Australian community setting. (June 2019) - Blignault, Ilse; Saab, Hend; Woodland, Lisa; Comino, Elizabeth
The cultural, linguistic, and religious diversity of Australia's population presents challenges for mental health service delivery. Arabic-speaking communities in Australia underutilise mental health services despite high levels of trauma and psychological distress. Clinicians who work with this population lack linguistically and culturally appropriate clinical resources. The aim of this study was to explore the acceptability and clinical utility of a Mindfulness Skills CD translated into formal Arabic. The 70 participants were Arabic-speaking adults, mostly Lebanese-born Muslim women, who enrolled in a 5-week mindfulness program using the CD and agreed to follow-up at 12 weeks. Both recruitment and data collection were undertaken by a female project officer who is a widely respected member of the Arabic community in south-east Sydney. Compliance with the program protocol was high and all but 4 participants continued to use the CD beyond the 5 weeks. Overall, participants reported that mindfulness techniques fitted well with their way of life and were compatible with their cultural and religious practices. Most found mindfulness complementary to their regular reflective prayer. Using the Mindfulness Skills CD was associated with statistically significant reductions in psychological distress as measured by the Kessler Scale (K10) and the Depression, Anxiety, and Stress Scale (DASS21) postprogram (K10; DASS21 Depression and Stress subscales) and at follow-up (all measures). The evaluation showed that the Arabic Mindfulness Skills CD is an effective and culturally appropriate mental health resource for this population group. This low-cost, easily distributed resource is suitable for use in individual self-management and as an adjunct to primary and specialist mental health care.